The Genus Nerine Herb. (Amaryllidaceae): Ethnobotany, Phytochemistry, and Biological Activity - Cahlíková, Lucie (Molecules, 2019)
Nerine Herbert, family Amaryllidaceae, is a genus of about 30 species that are native to South Africa, Botswana, Lesotho, Namibia, and Swatini (formerly known as Swaziland). Species of Nerine are autumn-flowering, perennial, bulbous plants, which inhabit areas with summer rainfall and cool, dry winters. Most Nerine species have been cultivated for their elegant flowers, presenting a source of innumerable horticultural hybrids. For many years, species of Nerine have been subjected to extensive phytochemical and pharmacological investigations, which resulted in either the isolation or identification of more than fifty Amaryllidaceae alkaloids belonging to different structural types. Amaryllidaceae alkaloids are frequently studied for their interesting biological properties, including antiviral, antibacterial, antitumor, antifungal, antimalarial, analgesic, cytotoxic, and cholinesterase inhibition activities. The present review aims to summarize comprehensively the research that has been reported on the phytochemistry and pharmacology of the genus Nerine.